2011
DOI: 10.1029/2011gl047737
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of assimilating CALIOP-derived aerosol extinction profiles on a global mass transport model

Abstract: Coupled two/three‐dimensional variational (2D/3DVAR) assimilation of aerosol physical properties retrieved from the Moderate Resolution Imaging Spectroradiometer (MODIS), Multi‐angle Imaging Spectroradiometer (MISR) and Cloud Aerosol Lidar with Orthogonal Polarization (CALIOP) satellite‐borne instruments is described for the U. S. Navy Aerosol Analysis and Prediction System (NAAPS) global aerosol mass transport model. Coupled 2D/3DVAR assimilation for NAAPS is evaluated for 48‐hr forecast cycles, computed four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 35 publications
2
69
0
Order By: Relevance
“…In particular, studies have shown notable improvements in aerosol forecasting through the assimilation of satellite aerosol products, mostly from daytime observations (e.g., Zhang et al, 2008aZhang et al, , 2011Zhang et al, , 2014Yumimoto et al, 2008;Uno et al, 2008;Benedetti et al, 2009;Schutgens et al, 2010;Sekiyama et al, 2010). To capture the diurnal cycle, the aerosol modeling community requires nighttime satellite aerosol data hav-ing broad spatial coverage and high temporal resolution to further advance aerosol, visibility, and air quality forecasts (e.g., Zhang et al, 2011Zhang et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, studies have shown notable improvements in aerosol forecasting through the assimilation of satellite aerosol products, mostly from daytime observations (e.g., Zhang et al, 2008aZhang et al, , 2011Zhang et al, , 2014Yumimoto et al, 2008;Uno et al, 2008;Benedetti et al, 2009;Schutgens et al, 2010;Sekiyama et al, 2010). To capture the diurnal cycle, the aerosol modeling community requires nighttime satellite aerosol data hav-ing broad spatial coverage and high temporal resolution to further advance aerosol, visibility, and air quality forecasts (e.g., Zhang et al, 2011Zhang et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2011) report mean global 0.550 µm AOD error at 12-h relative to AERONET near 0.075. However, this considers only the sunlit sector of the model at 12-h, where validation data are available, but with no assimilation having occurred at initialisation.…”
Section: Naaps Skill Versus Modis/misr and Aeronetmentioning
confidence: 99%
“…The vertical profile for aerosol particle electro-optical scattering, in particular, is a unique and highly synergistic satellite measurement, since passive aerosol-focused remote sensors alone are limited at best in observing vertically resolved information with reasonably high resolution. CALIOP profiling has, thus, benefitted a number of aerosol research initiatives, including global particle transport studies (e.g., Uno et al, 2009), surface emission estimates and injection scenario characterisation (e.g., Bessagnet et al, 2008;Amiridis et al, 2010), pyrocumulonimbus plume identification and dispersion (Fromm et al, 2010), volcanic plume monitoring (e.g., Carn et al, 2009;Campbell et al, 2012a), coupled two/three-dimensional variational (2D/3DVAR) data assimilation for global mass transport forecasting (e.g., Campbell et al, 2010;Zhang et al, 2011), four-dimensional ensemble Kalman filter data assimilation (e.g., Sekiyama et al, 2010), and transport model validation (e.g., Uno et al, 2008;Yumimoto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in aerosol climate studies (e.g., Kaufman et al, 2002;Zhang et al, 2005a, b) and aerosol and visibility forecasting (e.g., Zhang et al, 2008aZhang et al, , 2011Benedetti et al, 2009;Sekiyama et al, 2010) have responded to the growing demand for nighttime aerosol retrievals from satellite observations. For example, by using multisensor aerosol products from the Moderate Resolution Imaging Spectroradiometer (MODIS), the Multi-angle Imaging Spectroradiometer (MISR), and the Cloud Aerosol Lidar with Orthogonal Polarization (CALIOP), Zhang et al (2011) show improvements in aerosol forecasts using combined 2-D/3-D VAR aerosol assimilation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, by using multisensor aerosol products from the Moderate Resolution Imaging Spectroradiometer (MODIS), the Multi-angle Imaging Spectroradiometer (MISR), and the Cloud Aerosol Lidar with Orthogonal Polarization (CALIOP), Zhang et al (2011) show improvements in aerosol forecasts using combined 2-D/3-D VAR aerosol assimilation. Their study shows that higher forecast errors, measured by comparing modeled and AERONET aerosol optical depth (τ ) data, occur at the 12 and 36 h forecast ranges, possibly due in part to a lack of nighttime observations.…”
Section: Introductionmentioning
confidence: 99%